Принцип добросовестности в российском гражданском праве - Pechenkina, Nadezhda (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to present the functioning of the principle of good faith in the civil law of the Russian Federation. The author focus on the meaning of the good faith concept, its integrity and presumption